2021
DOI: 10.7717/peerj.12569
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of melon/squash graft junction reveals molecular mechanisms potentially underlying the graft union development

Abstract: Oriental melon (Cucumis melo var. makuwa Makino) has become a widely planted horticultural crop in China especially in recent years and has been subjected to the grafting technique for the improvement of cultivation and stress resistance. Although grafting has a long history in horticulture, there is little known about the molecular mechanisms of the graft healing process in oriental melon. This study aims to reveal the molecular changes involved in the graft healing process. In the present work, anatomical ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…It has also been reported that grafting induces differences in the transcriptome profile of grafted parents in plants, such as grapevines 39 , 40 . However, much attention had been absorbed on the connection of the graft union.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that grafting induces differences in the transcriptome profile of grafted parents in plants, such as grapevines 39 , 40 . However, much attention had been absorbed on the connection of the graft union.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq technology has been used to explore the potential transcriptional regulatory mechanisms of the graft healing process ( Cheong et al., 2002 ; Cookson et al, 2013 ; Liu et al, 2015 ; Chen et al, 2017 ; Melnyk et al, 2018 ; Mo et al, 2018 ; Xu et al, 2021 ). In order to further analyze the potential molecular networks of exogenous NAA regulating graft healing of oriental melon scion grafted onto squash rootstock, we performed the transcriptome analysis of graft junction at the IL, CA, and VB stage by CK vs. NAA using Melon genome and Cucurbita moschata (Rifu) genome, respectively, and deeply excavated the DEGs involved in hormone signal-transduction, ROS scavenging, and vascular bundle formation during graft union development ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA extraction, library construction, and RNA-Seq were performed by Biomarker Technology Co. (Beijing, China, https://www.biocloud.net/ ). RNA concentration was measured using NanoDrop 2000 (Thermo Fisher Scientific, Waltham, MA, USA), and the detailed protocol was previously described ( Xu et al, 2021 ). The raw sequencing data had been uploaded to the NCBI Sequence Read Archive (SRA) with the accession number PRJNA655799 and PRJNA689873 .…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomic analysis revealed the differential expression of 112 candidate unigenes involved in auxin and cytokinin signaling pathways in a study involving pecan graft healing (Qiu et al., 2016). Furthermore, transcriptomic analysis of the melon/pumpkin graft junction revealed that genes involved in hormone signaling and lignin biosynthesis play critical roles in graft healing (Xu et al., 2021). These studies suggest that transcriptome profiling may be used to study the molecular mechanisms involved in the engraftment process.…”
Section: Introductionmentioning
confidence: 99%